IMPLEMENTASI PERATURAN WALIKOTA KENDARI NOMOR 13 TAHUN 2008 TENTANG PENATAAN PEDAGANG KAKI LIMA DI KOTA KENDARI - Rian Supriadin; Syamsul Alam; La Ode Muhammad Elwan (Journal Publicuho, 2020)
The purpose of this research is to find out the Implementation of Kendari Mayor Regulation No. 13 of 2008 concerning the Arrangement of Street Vendors in Kendari City (Study of Mandonga District), as well as the factors that influence the Implementation of Street Vendor Merchant management policies in Mandonga District and the Constraints faced by the City Government Kendari in the Arrangement of Street Vendors in Mandonga District. The method used in this research is descriptive qualitative research method. All data in this study were obtained from interviews, observations and documentation. Based on what has been described in the results of the study, it can be concluded that in the implementation of the policy of the Mayor of Kendari Number 13 of 2008 concerning the arrangement of Street Vendors in Mandonga District conducted by related agencies namely the Department of Commerce, Cooperatives and SMEs of the City of Kendari, Civil Service Police Unit Praja Kendari City and Each Camat in Kendari City can be said to have not been maximized due to the lack of precise goals, aims and objectives of the policy regulated in Kendari Mayor Regulation No. 13 of 2008 concerning the arrangement of Street Vendors, which resulted in street vendors doing their activities, not in their place or a place that is legalized by the Kendari City Government.